Das Bestellerprinzip — Entlastung für den Mieter oder Augenwischerei? - Jochen Michaelis; Georg von Wangenheim (Wirtschaftsdienst, 2016)
Mit der Implementierung des Bestellerprinzips - wer den Makler beauftragt, mußs ihn auch bezahlen - hat der Gesetzgeber einen Wechsel der Zahllast für die Courtage vom Mieter zum Vermieter vorgenommen. Ob die intendierte Entlastung der Mieter gelingt, hängt maßgeblich vom Grad der Überwälzung auf die Miete ab. Auf der Verliererseite werden die Makler sein, da sie mit einer geringeren Nachfrage sowie einer Erosion der Courtage rechnen müssen. – – Real estate agents (REAs) brokering rent contracts in Germany charged fees only to tenants but not to landlords until 2015. In order to relieve tenants from this burden, German law now requires REAs to only charge landlords. We suggest three reasons for why landlords' brokerage fees are not simply passed on to tenants but declined substantially after the legal change as did the amount of brokering of rent contracts. REAs' bargaining power declined when landlords replaced tenants as bargaining partner. Brokerage fees to be paid by tenants serve as a self-selection mechanism of long term tenants. REAs' incentives to provide high quality decline when the price is fixed before they produce their service.
Keywords: R31; R38; K23; 330; Immobilienmakler; Provision; Mietenpolitik; Deutschland